STRATEGI PRODUK TENGTENG BERBASIS KEARIFAN LOKAL DALAM UPAYA MENGEMBANGKAN PEMASARAN UMKM SARI PUTRA DESASUKAMANAH - Harsanto, Prasetyo; Bahtiar, Dandi; Nurapipah, Dila Marwah (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2023)
This study aims to analyze the Tengteng product strategy to develop the marketing of Sari Putra SMEs in Sukamanah Village. The population in this study is Sari Putra SMEs, while the sample is the owners, employees, and consumers of Sari Putra SMEs, where there is one key informant and fifteen supporting informants. The data collection technique used a triangulation technique which consisted of observation, interview, and documentation with primary data and secondary data as the source of research data. Data analysis in this study uses the Fishbone Diagram Analysis model with assessment, data presentation from interviews with key informants and supporting informants, and then leveraging data and conclusions. The results showed that: (1) Tengteng product strategy based on local wisdom to develop marketing on product identity brands by 75% and brand rights by 31%, packaging attractiveness by 50%, innovation in product quality by 100%, product variants by 75% and design 69% products, 62% on product information labels and 100% halal certification. (2) the factors that hinder Tengteng's product strategy to develop marketing are 31% brand rights and 50% attractiveness of packaging. (3) innovations made by Sari Putra SMEs on local wisdom Tengteng products which consist of local materials, production, and marketing processes. (4) implementation of product strategies that are still simple using local marketing, production processes without machines, and lack of Human Resources in each part of production management does not yet have rights to Tengteng products because it is influenced by the marketing system of Tengteng products.